Best Proximity Point for α-ψ-Proximal Contractive Multimaps. (24th July 2014) - Ali, Muhammad Usman; Kamran, Tayyab; Shahzad, Naseer
Abstract : We extend the notions of α -ψ -proximal contraction and α -proximal admissibility to multivalued maps and then using these notions we obtain some best proximity point theorems for multivalued mappings. Our results extend some recent results by Jleli and those contained therein. Some examples are constructed to show the generality of our results.